Analysis of Cirebon City Economic Growth for Public Development of Community Development - Syaeful Bakhri; Pahrul Fauzi (EKO-REGIONAL, 2019)
The purpose of this study is to analyze trends in the economic growth sector in the city of Cirebon. The type of research used is a type of research with a quantitative approach. The location of this research was conducted in Cirebon City. Data obtained for this study were obtained from the results of literature studies and documentation techniques. Secondary data such as data from the Central Bureau of Statistics of Cirebon City are the main data used in this study. The data analysis technique used in the study of the economic growth of Cirebon City uses several stages such as identifying the driving factors and inhibitors of economic growth in the City of Cirebon through the location quotient analysis tool and the leading sector. The majority of economic sectors in Cirebon City are classified as the base or superior sectors, which are detected from the value of LQ statistic > 1. However, not all of these base sectors experience progress or positive developments. There are only three sectors (social health service, communication information, and company service) that are classified as the base sector and have positive dynamics and growth.Keywords: Economic Growth, Leading Sector, Cirebon.